2014
DOI: 10.5964/ejop.v10i3.682
|View full text |Cite
|
Sign up to set email alerts
|

The Humor Styles Questionnaire in Italy: Psychometric Properties and Relationships With Psychological Well-Being

Abstract: This study investigated the psychometric properties of the Humor Styles Questionnaire (HSQ) and the relation between humor and psychological well-being within the context of Italy. A total of 293 (178 females, 115 males) Italian high school and undergraduate university students – whose ages ranged from 14 to 25 years – completed the Italian versions of the HSQ and the Ryff’s Psychological Well-Being scales (RPWB). The HSQ scale reliabilities were generally acceptable, and intercorrelations among the scales wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 60 publications
5
21
0
3
Order By: Relevance
“…The internal consistency (Cronbach's alpha) of the four subscales ranged from acceptable (.72) to good (.85). These values are in accord with the validation report of the original scale (.77 to .81;Martin et al, 2003); with the Italian version of the scale, ranging from .50 to .85 (Sirigatti, Penzo, Giannetti, & Stefanile, 2014); with the German version of the scale, ranging from .70 to .87 (Ruch & Heintz, 2016); with Arabic version of the HSQ, ranging from .55 to .79 (Taher, Kazarian, & Martin, 2008), as well as with the Belgian (French) version of the scale, ranging from .70 to .75 (Saroglou & Scariot, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The internal consistency (Cronbach's alpha) of the four subscales ranged from acceptable (.72) to good (.85). These values are in accord with the validation report of the original scale (.77 to .81;Martin et al, 2003); with the Italian version of the scale, ranging from .50 to .85 (Sirigatti, Penzo, Giannetti, & Stefanile, 2014); with the German version of the scale, ranging from .70 to .87 (Ruch & Heintz, 2016); with Arabic version of the HSQ, ranging from .55 to .79 (Taher, Kazarian, & Martin, 2008), as well as with the Belgian (French) version of the scale, ranging from .70 to .75 (Saroglou & Scariot, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…In the German study (Ruch & Heintz, 2016) statistically significant correlations between affiliative and self-enhancing humor (r = .39 vs. .47 in the current work), affiliative-and aggressive humor (.23 vs. .19 here), affiliative-and self-defeating (.10 vs. .08 here), and aggressive and self-defeating (.31 vs. .26) were found. Similarly, the results of the Italian validation study (Sirigatti et al, 2014) showed positive and significant correlations between affiliativeand self-enhancing humor (from r = .39 to .26 in different samples vs. .47 for the whole sample here), between affiliative-and aggressive humor (from r = .16 to .34 in different samples, vs. .19 for the whole sample here), between self-enhancing and aggressive humor (for males and young adults r = .29 vs. .005 for the whole in our work), and between self-enhancing-and selfdefeating humor (for males r = .19 vs. .15 for the whole sample here). Finally, the between-subscales correlations obtained in the Arabic validation study (Taher et al, 2008) of the HSQ are also in accord with the values obtained in our current work: affiliative-and self-enhancing humor (.41 vs. .47 here), affiliative-and aggressive humor (.10 vs. .19 here), affiliative-and selfdefeating humor (.19 vs. .08 here), self-enhancing-and aggressive humor -.01 vs. .005 here), self-enhancing-and self-defeating humor (.21 vs. .15 here), and self-defeating and aggressive humor (.36 vs. .26 here).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Evidencia sobre esta estructura del humor de cuatro dimensiones ha sido recabada en diferentes culturas y poblaciones: canadiense (Martin et al, 2003), argentina (Lillo, 2006), libanesa (Taher, Kazarian & Martin, 2008); italiana (Sirigatti, Penzo, Giannetti & Stefanile, 2014), austriaca y alemana (Stieger, Formann, & Burger, 2011), israelita (Zeigler-Hill & Besser, 2011, china (Yue et al, 2014;Zhao et al, 2012Zhao et al, , 2014, o taiwanesa (Chiang, Sheng, Wu, & Yen, 2014).…”
Section: Introductionunclassified
“…Al analizar las relaciones entre humor y sexo Martin et al (2003) y Sirigatti et al (2014) encontraron puntuaciones más altas del estilo de humor mal adaptado en los hombres, mientras que las mujeres encontraron puntuaciones más altas en el estilo de humor más adaptativo. Estos resultados se corresponden con las tendencias de otras investigaciones donde indican que los hombres se involucran más en estilos de humor de corte inadaptado en comparación con las mujeres (Crawford y Gressley, 1991;Martin y Kuiper, 1999).…”
Section: Introductionunclassified